2007
DOI: 10.1166/jnn.2007.721
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Pressure-Induced Transformation of Boron Nitride Nanotubes

Abstract: We have used Raman spectroscopy to study the behavior of multi-walled boron nitride nanotubes and hexagonal boron nitride crystals under high pressure. While boron nitride nanotubes show an irreversible transformation at about 12 GPa, hexagonal boron nitride exhibits a reversible phase transition at 13 GPa. We also present molecular dynamics simulations which suggest that the irreversibility of the pressure-induced transformation in boron nitride nanotubes is due to the polar nature of the bonds between boron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
2
9
2
Order By: Relevance
“…As shown in Figure S2a of the Supporting Information, the evolution of the E 2g mode energy is linear up to the maximum pressure detected of 24 GPa with a slope of and an ambient-pressure intercept frequency at 1368 ± 1 cm –1 , in good agreement with the TM frequency of 1365 ± 2 cm –1 measured outside of the cell. The obtained pressure slope for the E 2g is in good agreement with the values obtained in a previous works. , Nevertheless, we note that, in the work of Saha et al, deviations from linearity were observed from 10 GPa and the TM signal was lost at 12 GPa, i.e., at a pressure 2 times smaller than in our measurements. In Figure b is shown the corresponding pressure evolution of the full width at half maximum (FWHM) of the E 2g mode.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As shown in Figure S2a of the Supporting Information, the evolution of the E 2g mode energy is linear up to the maximum pressure detected of 24 GPa with a slope of and an ambient-pressure intercept frequency at 1368 ± 1 cm –1 , in good agreement with the TM frequency of 1365 ± 2 cm –1 measured outside of the cell. The obtained pressure slope for the E 2g is in good agreement with the values obtained in a previous works. , Nevertheless, we note that, in the work of Saha et al, deviations from linearity were observed from 10 GPa and the TM signal was lost at 12 GPa, i.e., at a pressure 2 times smaller than in our measurements. In Figure b is shown the corresponding pressure evolution of the full width at half maximum (FWHM) of the E 2g mode.…”
Section: Resultssupporting
confidence: 93%
“…The obtained pressure slope for the E 2g is in good agreement with the values obtained in a previous works. 49,50 Nevertheless we note that in the work of Saha et al 49 deviations from linearity were observed from 10 GPa and the TM signal was lost at 12 GPa, i.e., at a pressure two times smaller than in our measurements. In Fig.…”
Section: Raman Spectroscopycontrasting
confidence: 56%
See 1 more Smart Citation
“…26 Particularly intriguing is the surprising superhardness (i.e., harder than natural diamond) recently predicted for w-BN, which is similar to that for lonsdaleite (hexagonal diamond). 23 However, very few highpressure studies of BNNTs have been reported, [27][28][29] in contrast to the numerous investigations of CNTs under high pressure, for which Raman spectroscopy was used as the most effective characterization probe. 30 More importantly, because of the close proximity of the extremely intense T 2g mode (1334 cm -1 ) of diamond to the major Raman mode (E 2g ) of BNNTs (∼1367 cm -1 ), 27,28,31,32 monitoring pressure-induced transformations in diamond anvil cells (DACs) by Raman spectroscopy is, therefore, subject to some ambiguity.…”
Section: Introductionmentioning
confidence: 99%
“…ZnS Nanobelt t: ~10 nm w: ~1 m l: 100 m 0-11.4 X-ray diffraction Nanorod w: ~10 nm 0-19.4 Raman, Photoluminescence (Li et al, 2007) w: ~10 nm 0-37.2 X-ray diffraction (Li et al, 2011) BN Nanotube d: 20-50 nm 0-16 Raman (Saha et al, 2007;Saha et al, 2006) d: ~ 50 nm 0-19.1 X-ray diffraction (Muthu et al, 2008) d: ~ 100 nm 0-34.6 FTIR ZnO Nanowire w: 60-100 nm l: tens of m 0-21.5 Raman, X-ray diffraction (Yan et al, 2009) Nanotube d:10-70 nm 0-21.5 X-ray diffraction (Hou et al, 2009) SnO 2 Nanowire w: 50-60 nm l: several m 0-37.9 Raman, X-ray diffraction (Dong & Song, 2009) Nanobelt t: tens of nm w: ~1m l: several m 0-36. 2 Raman, X-ray diffraction (Dong & Song, 2009) TiO 2 Nanoribbon t: ~20 nm w: 50-200 nm l: tens of m 0-30.9…”
Section: Methods Referencementioning
confidence: 99%